KINERJA MESIN PENGERING MIKRO BERTENAGA KOMBINASI SURYA DAN LISTRIK DALAM PENGERINGAN KAYU JATI - Galit Gatut Prakosa; Ramli Ramadhan (BRIN Publishing, 2021)
Indonesia is one of the exporting countries for wood crafts to 193 countries, but in the process, it often suffers losses due toproduct returns by the buyer due to cracked defects when the goods arrive at the ordering country. One of the efforts to improve thequality of wood crafts is to dry the wood according to the destination country so that the dimensions and humidity are relativelystable. The industrial-scale wood drying process requires a high investment, so developing a small-scale dryer for artisans is necessary.This study aims to design and test the performance of a simple wood dryer with a capacity of 1.5 m³ at an affordable cost, easy tooperate and use by the public. The test samples used were stems and branches of teak (Tectona grandis L.f.). The heater used isa combination of solar heat and electricity, namely the heat of the sun is maintained and flowed into the wood drying chamberthrough a fan that sucks hot air from the combustion chamber into the drying chamber. Hot air is circulated to the inlet againcontinuously to be redistributed to the drying chamber. The test results show that the daily average temperature of solar heat receivedby the drying chamber is between 40−50°C, while the temperature for drying teak wood is between 45−70°C. From the evaluationthat has been done, the heating plate is less effective in heating the space, so it is necessary to replace it with a modification of theinstallation of the heating element on battery powered devices.